(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Language has been affected by the significant trend ofglobalization considerably in the last two decades. Literally, we haverevolutionary changes in communication and technology in 21st century andlanguage has played a vital role to enable us to achieve and experience thesedevelopments. It is imperative that only powerful languages, like English, takethe lead and stay on top in a global society and undoubtedly English has playeda dominant role in international politics and diplomacy, informationtechnology, science and technology, education and in resolving internationalconflicts and also the world economy. In this globalization, English hasemerged as an international language despite strong competition from otherlanguages.